Hydrogel Arrays and Choroidal Neovascularization Models for Evaluation of Angiogenic Activity of Vital Pulp Therapy Biomaterials - Saghiri, Mohammad Ali (J Endod, 2018)
INTRODUCTION: This study intended to evaluate the angiogenic properties of vital pulp therapy materials including white mineral trioxide aggregate (WMTA), calcium hydroxide (Ca(OH)(2)), Geristore, and Nano WMTA biomaterials. METHODS: WMTA, Ca(OH)(2), Geristore, Nano WMTA disks were prepared, dispersed into 2 mL of MiliQ distillated water, and centrifuged to obtain 2 mL supernatant elution. Thirty five wells of poly ethylene glycol (PEG) hydrogel arrays were prepared and divided into five groups of seven (n=7). Mice molar endothelial cells (EC) were placed on hydrogel arrays. The elution prepared from each sample was diluted in growth medium (1:3) and was added to the hydrogel arrays. The EC medium alone was used for control. For choroidal neovascularization (CNV) model, thirty five 6-week-old female mice were lasered, divided into five groups, and elution from each sample (2 μl) or saline (control) was delivered by intravitreal injection on day of laser and one week later. The mean number of nodes and total branches length in hydrogel arrays, and mean area of CNV, were calculated using ImageJ software and analyzed by one-way ANOVA and Post hoc Tukey HSD tests. RESULTS: The comparison of results of number of nodes showed the values of control > Geristore > Nano WMTA > WMTA > Ca(OH)(2). In total branch length and CNV area, the comparison of results showed values of Geristore > control > Nano WMTA > WMTA > Ca(OH)(2). CONCLUSIONS: All tested materials showed minimal antiangiogenic activity, while Geristore and Nano WMTA showed higher proangiogenic activity than WMTA and Ca(OH)(2).